Evaluation of a customised organic fertilizer in relation to labile carbon dynamics nutrient release characteristics and productivity of banana - Naveen Leno (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2017)
A study entitled ‘Evaluation of a customised organic fertilizer in relation to labile carbon dynamics, nutrient release characteristics and productivity of banana’ was carried out at the Department of Soil Science and Agricultural Chemistry, College of Agriculture, Vellayani, during 2013-16. The objective of the study was to evaluate the customised organic fertilizer obtained from biodegradable urban garbage by rapid thermochemical conversion technology, in relation to labile carbon dynamics, nutrient release characteristics and productivity of banana in agro- ecological unit 8 of Kerala. Characterisation and assessment of the maturity parameters of degradable solid waste and the organic fertilizer produced from it were done. Organic fertilizer produced by thermo chemical treatment was odourless, with a particle size of < 4mm, low moisture content and bulk density compared to raw waste. It recorded a neutral pH, low electrical conductivity and total organic carbon. The content of major nutrients was higher in the organic fertilizer. Status of secondary and micronutrients was sufficient and heavy metal contents were within safe limits. Cellulose content in organic fertilizer decreased by 38.14% whereas hemicellulose and lignin contents increased. Organic fertilizer recorded lower C:N ratio, C:P ratio, NH4+/NO3- ratio, water soluble carbon/total organic carbon ratio and a higher cation exchange capacity in comparison to degradable solid waste. The humification indices were higher and was non phytotoxic. Fertilizing Index of 4.7 and Clean Index of 5.0 qualify it to be a Class A marketable organic fertilizer. Customisation of the organic fertilizer was done on the basis of soil test and crop requirement for Nendran banana in AEU 8. A laboratory incubation experiment to study the nutrient release characteristics of the customised organic fertilizer was done for a period of 300 days with seven treatments, of which three were FYM based, three customised organic fertilizer based with a soil alone (control) treatment. Regardless of the source of organic manure, the organic carbon content remained high in all the manured treatments than in soil alone. N release pattern indicated steady and constant supply of the nutrient. A phase of total immobilization of P was observed from 180 to 240 days in all treatments. Ca also exhibited a similar trend. The release pattern of K and Mg was identical with a progressive mineralization up to 240 days. Trend in release pattern of S was almost similar to N with a 90 days immobilization-mineralization cycle. Micronutrient kinetics exhibited a series of shorter mineralization-immobilization cycles at 60 days interval. However an increasing trend in release of B and Fe was observed till the end. Mn and Zn followed a homogenous release pattern with highest availability at 20 days after incubation. A field experiment of Nendran banana was laid out with 8 treatments in RBD to study the effect of customised organic fertilizer on labile carbon dynamics and yield. Temporal variation in organic carbon revealed long duration cycles with smooth curves representing heterogeneous and buffered field condition. The treatment in which customised organic fertilizer was used for basal and top dressing, contained high labile carbon, non labile carbon and carbon pool index. Soil reaction (pH) and water holding capacity of customised organic fertilizer based treatments and EC of FYM treatments increased with the growth stages. Antagonism between K and Ca was evident. The availability of micronutrients increased initially and reached the lowest at harvest stage. B steadily decreased up to harvest. Application of customised organic fertilizer enhanced dehydrogenase activity. Foliar concentration of N and P were highest in the initial stages in these treatments while that of K was highest at the later stages of crop growth. Foliar Ca and S also recorded higher values in these treatments. A synergistic effect was observed in the uptake of B and Mg and similarly between Mn and Zn. While Cu absorption was more during vegetative phase, Fe absorption coincided with flag leaf formation. The treatment where customised organic fertilizer was used for basal application as well as top dressing recorded highest plant growth characters, total dry matter production, shelf life of fruits and B:C ratio but was on par with the treatment which received FYM (soil test basis) in bunch weight, number of fingers per bunch and length of peduncle. Hence it can be concluded that the customised organic fertilizer obtained from degradable solid waste is of class A marketable quality, capable of a steady and constant supply of all essential nutrients to banana and realising profitable net returns, ensuring immediate energy source to rhizospheric microorganisms and promoting long term carbon sequestration in agro-ecological unit 8 of Kerala.